Replacing Fish Oil with Hydrogenated Soybean Oils in Feeds for Yellowtail. (23rd April 2018) - Bergman, Alexis M.; Trushenski, Jesse T.; Drawbridge, Mark
Abstract: To assess the relative merits of monounsaturated fatty acid (MUFA)‐rich versus saturated fatty acid (SFA)‐rich lipids as alternatives to fish oil in aquafeeds, diets formulated for Yellowtail Seriola dorsalis —containing menhaden fish oil, fully hydrogenated soybean oil (high SFA content), partially hydrogenated soybean oil (high MUFA content), or blends of these soy‐derived lipids (20/80, 40/60, 60/40, or 80/20)—were tested in a 7‐week feeding trial. Juvenile fish ( 11 g) were stocked in a semi‐closed recirculating aquaculture system (15 fish/tank), diets were randomly assigned to tanks in triplicate ( N = 3), and fish were fed in slight excess of estimated apparent satiation. Growth performance did not vary based on dietary SFA versus MUFA content, but performance was inferior among fish fed the soybean oil‐based feeds relative to those fed the fish oil‐based feed: weight gain was 714–770% versus 848%; specific growth rate was 4.03–4.16% versus 4.32% body weight/d; and feed conversion ratio was 1.30–1.38 versus 1.27. Generally, fillet fatty acid composition mirrored dietary composition except that the fillets of fish fed diets containing primarily fully hydrogenated soybean oil contained fewer SFAs and more long‐chain polyunsaturated fatty acids (LC‐PUFAs) than one would expect based on dietary fatty acid profiles. Fillets of fish that were fed partially hydrogenated soybean oil contained trans‐fatty acids (0.02–0.06 g of trans fats per 100 g of fillet) but only at trace levels. Liver fatty acid profiles were less affected by dietary lipid source, but where differences existed, they followed patterns similar to those observed in fillets. Results suggest that blends of fully and partially hydrogenated soybean oils may yield slightly higher growth performance and fillet lipid content without accumulating enough trans fats to negatively affect consumers. Diets containing only fully hydrogenated soybean oil may slightly reduce lipid digestion in Yellowtail, but they mitigate LC‐PUFA loss associated with fish oil sparing.